RT-PCR ANALYSIS OF GENES EXPRESSION TO EVALUATE THE BIOMEDICAL IMPORTANCE OF MEDICAL-HERBAL EXTRACTS IN DIABETES TREATMENT - Salah-Eldin, Alaa-Eldin; Ibrahim, Marwan A.; Soliman, Mohamed M. (European Scientific Journal, ESJ, 2015)
Fenugreek is an annual crop belonging to the legume family grown in most parts of the world. It is known to possess a number of medicinal properties, but a little phytochemical research has been carried out on the seeds of species; Trigonella hamosa Leguminosae. Previously we reported that Trigonella seeds extract are shown to have hypoglycemic effects on experimental diabetic rats. The aim of the current study is to understand the molecular mechanism of antidiabetic actions of Trigonella. Therefore, we examined the expressions levels of genes involved in glucose metabolism in liver of diabetic rats. Upon this basis, streptozotocin (STZ)-diabetic rats are used to assess hepatic glucokinase (GCK), insulin like growth factor-1 (IGF- 1), and glucose transporters (GLUT-2) genes expressions after Trigonella administration by oral intragastric intubation for two months, using RT-PCR assay. The current findings demonstrated that Trigonella reduced significantly glucose level in diabetic rats, while significantly increases insulin serum level. GCK expression levels in hepatic tissue of diabetic-rats are found to be suppressed, while Trigonella treatment induces an increase in hepatic GCK activity. Diabetes due to STZ has a little effect on IGF-1 gene expression, while Trigonella administration elevates mRNA expression significantly. On the other hand, Trigonella reduce and normalize the elevation of GLUT-2 gene expression, which increased due to STZ treatment. These results indicated that Trigonella are powerful antidiabetic agent, induce hypoglycemia by up-regulation of CGK and IGF-1 genes expression and induce an insulin mimetic activity.